2023
DOI: 10.3390/ijms241914625
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Embryogenic and Non-Embryogenic Callus Provides New Insight into the Nature of Recalcitrance in Cannabis

Mohsen Hesami,
Marco Pepe,
Maxime de Ronne
et al.

Abstract: Differential gene expression profiles of various cannabis calli including non-embryogenic and embryogenic (i.e., rooty and embryonic callus) were examined in this study to enhance our understanding of callus development in cannabis and facilitate the development of improved strategies for plant regeneration and biotechnological applications in this economically valuable crop. A total of 6118 genes displayed significant differential expression, with 1850 genes downregulated and 1873 genes upregulated in embryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…However, as the concentration increased, KIN demonstrated a dose-dependent response, leading to enhanced callus formation rate and fresh weight of callus. This suggests that KIN might play a PLOS ONE role in modulating cell division and proliferation processes during callogenesis [9,69,70]. Moreover, our study explored the effect of NAA and IBA, two auxins, on callus formation rate and callus fresh weight in petunia.…”
Section: Discussionmentioning
confidence: 96%
“…However, as the concentration increased, KIN demonstrated a dose-dependent response, leading to enhanced callus formation rate and fresh weight of callus. This suggests that KIN might play a PLOS ONE role in modulating cell division and proliferation processes during callogenesis [9,69,70]. Moreover, our study explored the effect of NAA and IBA, two auxins, on callus formation rate and callus fresh weight in petunia.…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al identified the upregulation of auxin synthesis-related genes (e.g, GH3.6 and PCO2 ) and the downregulation of cytokinin dehydrogenase ( CKX6 and CYP450 ) genes in the SE of in Paeonia ostii 'Fengdan' using transcriptome sequencing technology [ 14 ]. Hesami and colleagues used transcriptome sequencing and identified 1,850 genes downregulated and 1,873 genes upregulated in embryogenic callus compared to non-embryogenic callus of cannabis [ 15 ], including 42 different TF classes (e.g., MYB, C2H2, ERF, AP2, bHLH, bZIP, B3, WRKY and GRAS ). Hou et al used LC-MS/MS (liquid chromatography with tandem mass spectrometry) and identified 6,269 differentially expressed proteins (DEPs) in three stages (the primary embryogenic callus, the single embryo, and the cotyledon embryo) of SE in Larix olgensis , including 18 TF families were identified, including 18 TFs from the AP2, NAM and WOX families [ 16 ].…”
Section: Introductionmentioning
confidence: 99%